School Alienation: A Construct Validation Study - Julia Morinaj; Jan Scharf; Alyssa Grecu; Andreas Hadjar; Tina Hascher; Kaja Marcin (EARLI, 2017)
Early identification of school alienation is of great importance for students' educational outcomes and successful participation in society. This study examined the psychometric characteristics of a newly developed assessment instrument, the School Alienation Scale (SALS), to measure school alienation among primary and secondary school students. The SALS consists of three school-related domains, namely, classmates, teachers, and learning. Based on the responses of Swiss (1) and Luxembourgish (2) students from two school-specific cohorts - primary (grade 4; n1=486, n2=503) and secondary schools (grade 7; n1=550, n2=534), we assessed instrument reliability, validity, and cross-cultural equivalence. The scale showed evidence of reliability and internal validity across two samples, confirming that the hypothesized first-order three-factor model fits the data better than several alternative models. The results of measurement invariance tests revealed that the measurement model operated equally well for primary and secondary school students in both countries. The construct validity of the SALS was additionally supported by demonstrated criterion-related validity. Specifically, school alienation domains were negatively associated with positive attitudes to and enjoyment in school; social problems in school were positively related to alienation from classmates and teachers. Our key contributions to the measurement of school alienation are the disclosure of the core domains of school alienation, development of a reliable and valid instrument, and justification for its use. Therefore, the results of this study have important implications for further theoretical work in alienation research and contribute to comparative research by examining the construct of school alienation in different educational settings.